Trace metal pollution assessment in the surface sediments of nearshore area, off Calicut, southwest coast of India. Issue 1 (15th July 2017) - Srinivas, Reji; Shynu, R.; Sreeraj, M.K.; Ramachandran, K.K.
Abstract: Metal concentrations (Al, Cr, Ni, Cu, Zn, and Pb), grain size, and total organic carbon content in 29 surface sediment samples from the nearshore area off Calicut were analyzed to determine their distribution and pollution status. Surface sediments were dominantly silts with low percentage of clay and sand at nearshore and offshore areas. The mean metal concentrations were in the following order: Cr > Ni > Zn > Pb > Cu. The enrichment factor and geo-accumulation index of metals suggest that the surface sediments were not polluted by Zn and moderately polluted by Cu and Ni. By contrast, Cr and Pb showed significant enrichment levels. Results from a multivariate statistical analysis suggested that the spatial enrichment of these heavy metals was related to sediment type. Thus, the sediment distribution and their metal enrichment were mainly controlled by local hydrodynamic conditions that caused the winnowing of fine-grained sediments. Highlights: Determined the metal distribution and pollution status of surface sediments. Surface sediments were dominantly silts with low percentage of clay and sand. The mean metal concentrations decreased in the following order: Cr > Ni > Zn > Pb > Cu. Spatial enrichment of the heavy metals was related to sediment type.